Expression of p53, Ki-67, and CD31 proteins in endometrial polyps of postmenopausal women treated with tamoxifen. - Miranda, Sergimar P; Traiman, Paulo [UNESP]; Cândido, Eduardo B; Lages, Elisa L; Freitas, Gustavo F; Lamaita, Rívia Mara; Vidigal, Paula V T; Silva Filho, Agnaldo Lopes da [UNESP] (My University, 2010)
This study was undertaken to investigate the expression of p53, Ki-67, and CD31 proteins in endometrial polyps of postmenopausal women treated with tamoxifen (TAM). Postmenopausal women with endometrial polyps treated with TAM (n = 20), postmenopausal women with endometrial polyps without hormone use (n = 20), postmenopausal women with atrophic endometrium (n = 20), and postmenopausal women with endometrial adenocarcinoma (n = 20) were prospectively investigated. Tissue samples were immunohistochemically evaluated by monoclonal antibodies for p53, Ki-67, and CD31. The data were analyzed using the Student t test, analysis of variance, and χ2 to evaluate significant differences between the groups. The level of significance was set at P < 0.05. There was no difference in the expression of p53 between the groups (P = 0.067). The expression of Ki-67 was higher in the polyp samples from TAM-treated women compared with those from the women using no hormone (P = 0.0047) and those from the women with atrophic endometrium (P = 0.008). Samples from the women with endometrial cancer was associated with higher Ki-67 expression compared with the polyp samples from TAM-treated women (P = 0.004). The expression of CD31 was higher in the polyp samples of TAM-treated women compared with that of the samples from the women with atrophic endometrium (P < 0.001) and similar to the polyp samples from the women using no hormone (P = 0.319) and to the samples from the women with endometrial cancer (P = 0.418). The use of TAM in postmenopausal women might be associated with increased cellular proliferation in endometrial polyps without interfering angiogenesis or inactivation of tumor suppressor proteins.
Keywords: antineoplastic hormone agonists and antagonists; CD31 antigen; Ki 67 antigen; pharmacological biomarker; protein p53; tamoxifen; tumor marker; tumor protein; adenocarcinoma; aged; drug effect; endometrium; endometrium tumor; evaluation; female; human; metabolism; middle aged; pathology; polyp; postmenopause; prognosis; Adenocarcinoma; Aged; Aged, 80 and over; Antigens, CD31; Antineoplastic Agents, Hormonal; Biomarkers, Pharmacological; Endometrial Neoplasms; Endometrium; Female; Humans; Ki-67 Antigen; Middle Aged; Neoplasm Proteins; Polyps; Postmenopause; Prognosis; Tamoxifen; Tumor Markers, Biological; Tumor Suppressor Protein p53